Key Factors for the Sustainable Production of Swiftlet Birds’ Nest Industry in Malaysia: A Case Study in Northern Peninsular Malaysia - Roslina Kamaruddin; Che Engku Mansor Che Engku Ismail; Siti Aznor Ahmad (International Journal of Supply Chain Management, 2019)
Swiftlet bird’s nest plays significant role towards economic growth of the country and development of the industry becomes paramount. The objective of the study is to identify the key factors that contribute to the sustainable swiftlet nest production. A total of 223 swiftlet entrepreneurs were simple randomly selected from the study area. Descriptive statistics was used to identify the socio-economic characteristics of respondents and structural equation modelling was used to identify the factors that contribute to sustainable swiftlet production. Results revealed that most of the respondents were above 40 years old while almost half of the respondents have higher secondary school education. Livelihood assets, role of middlemen and role of institution were statistically significant in influencing sustainable production of swiftlet nest. These finding recommends for active monitoring and advisory services by relevant institutions and information dissemination about trainings to enhance producers’ technical knowledge on swiftlet rearing. Indirectly this will improve the physical facilities, financial management skill and social networking of swiftlet producer in order to sustain their production. Likewise, middlemen should be enlightened more about their role in the marketing of swiftlet bird’s nest and monitored by relevant authorities.